Prognostic Factors Influencing the Efficacy of Regorafenib in the Treatment of Metastatic Colorectal Cancer - Nadiye SEVER; İbrahim Vedat BAYOĞLU (Namık Kemal Tıp Dergisi, 2025)
Aim: Metastatic colorectal cancer (mCRC) remains a significant clinical challenge for patients who have exhausted standard treatment options. Regorafenib, an oral multikinase inhibitor, is approved for use in refractory with mCRC patients; however, its real-world efficacy continues to be an area of ongoing research. This study aimed to evaluate the efficacy and clinical outcomes of regorafenib in mCRC patients. Materials and Methods: This retrospective study assessed the efficacy of regorafenib in mCRC patients who had progressed after at least two lines of systemic therapy. A total of 120 patients were included in the study. Univariate and multivariate analyses of factors affecting survival were conducted using the Cox regression models. Results: Of the patients, 46 (38.3%) were female and the median age was 58 years. The median progression-free survival (PFS) was 3.38 months and the median overall survival (OS) was 8.01 months. Age and BRAF mutation status were determined as important prognostic factors for PFS. Patients under 65 years of age had a shorter PFS compared to patients aged 65 years and older (p=0.045). Patients with BRAF mutations exhibited significantly shorter PFS compared to those without the mutation (1.84 vs. 3.41 months, p=0.014). In OS analysis, ECOG score (p=0.022), regorafenib dose reduction (p=0.005) and carbohydrate antigen 19-9 (CA19-9) level (p=0.004) were independent prognostic factors. KRAS and NRAS mutations, primary tumor localization and prior targeted therapies combined with chemotherapy did not significantly affect PFS or OS. Conclusion: Regorafenib is an effective option for the treatment of mCRC in third-line and beyond. ECOG performance status, regorafenib dose adjustment and CA19-9 levels are significant factors influencing survival.